Global Minimum Corporate Tax – Developing Countries Beware - Thabo Legwaila (Obiter, 2025)
In July 2021, under the auspices of the Organisation for Economic Co-operation and Development and the Group of Twenty Countries (the G20), a group of 130 countries reportedly representing more than 90 per cent of global gross domestic products joined in establishing a two-pillared package. This package aims to curb base erosion and profit shifting and ensure that large Multinational enterprises (MNEs) pay taxes where they operate and earn profits. The aim was to add much-needed certainty and stability to the international tax system. Pillar One relocates some MNE profits to the user or market jurisdiction. Pillar Two proposes a global minimum corporate tax which is intended to neutralise the incentives to shift profits based solely on tax outcomes. The author finds that despite its global impact, the global minimum tax has been designed by, and for only a small number of wealthy countries. As a result, the benefits thereof can only be viewed from the perspective of those benefitting countries, before one considers any residual benefits for the unintended participants, the developing countries. This article explores the effects and disadvantages of the proposed minimum tax, with a specific focus on developing countries, and concludes that the benefits of minimum tax for developing countries are not patent, clear, or determinable. The disadvantages of the global minimum tax for developing countries include challenges to fiscal sovereignty, depriving developing countries of the ability to use taxes to compete with developed countries as well as the high cost of implementation. The article explores alternatives to the minimum tax and concludes by proposing various options that developing countries should consider to curb international tax avoidance.